A System for Filling Store Displays: Pitting a Single Model against a Set of Demand Forecasting Models - Myna, Artur; Myna, Jacek (System zapełnienia ekspozycji sklepowych: pojedynczy model a zespół modeli prognozowania popytu, 2023)
The aim of the paper was to develop the concept of retail display space allocation as a system and to assess the quality of very slow-moving products demand forecasting models (that have not yet been used by retail companies in Poland) as its key subsystem. Forecasts were made using the example of a clothing company. The quality of these models was assessed using the Weighted Mean Absolute Percentage Error. The first step was to build the individual models. Later, the authors built separate models for brick-and-mortar and online stores as well as brands, creating a set of six models. The findings show that the classification approach for very slow movers provides as precise results as the regression approach. No single model or set of models (built with a particular machine learning method) could be identified that made the best demand forecasts for brick-and-mortar stores, as statistical tests generally did not confirm the significance of the differences between the median forecasts.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 2, s. 96-106
Keywords: Extreme Gradient Boosting; logistic regression; random forests; regresja logistyczna; las losowy